Physico-Chemical and Texture Properties of Gelatin-Free Jelly Desserts - Nepovinnykh N.; Petrova O.; Belova N.; Yeganehzad S. (Техника и технология пищевых производств)
The research features the technological challenge of producing jelly desserts by replacing gelatin by non-starch polysaccharides of plant, bacterial, and algal origin (separately or in binary mixtures) in order to overcome religious and ethical constraints. The authors focused on the texture which is responsible for gel network formation of desserts. Hydrocolloids are widely used in many food formulations to improve quality attributes and shelf-life. The polysaccharides under analysis included alginate, pectin, iota-carrageenan, konjac glucomannan, xanthan, and guar gum, separately or in binary mixtures. The experiment made it possible to determine polysaccharides and their optimal concentrations (konjac glucomannan 0.4 % : xanthan gum 0.6 %; locust bean gum 0.2 % : xanthan gum 0.8 %; iota-carrageenan 0.4 %) as gelling agents for the production of desserts without gelatin. Formation of a gel network in desserts occurs as a result of a complex interaction of hydrocolloids, milk fat, and sugar. Structure formation of jelly desserts with polysaccharides occurs already at 18 ± 2°C in 20–40 minutes. In contrast, the structure formation of the control sample occurred at 4 ± 2°C in 2–3 hours. Sensory evaluation of the products was conducted by panellists according to the following criteria: taste, colour, consistency, aroma, and appearance. The paper also describes an analysis of texture indicators. The shelf-life was assessed according to moisture content and water activity as 24 hours at 4 ± 2°C. Several economically-viable new formulations were identified: they successfully reproduced the essential attributes of well-established and widely-consumed traditional gelatin desserts.